Combatting Social Isolation Among Older Adults in a Time of Physical Distancing: The COVID-19 Social Connectivity Paradox - Smith, Matthew Lee; Steinman, Lesley E.; Casey, E. A. (Frontiers in Public Health, 2020)
Social isolation is an important public health issue that has gained recognition during the COVID-19 pandemic because of the risks posed to older adults based on physical distancing. The primary purposes of this article are to provide an overview of the complex interconnectedness between social isolation, loneliness, and depression while introducing the COVID-19 Connectivity Paradox, a new concept used to describe the conflicting risk/harm continuum resulting from recommended physical distancing. In this context, examples will be provided for practical and feasible community-based models to improve social connectivity during COVID-19 by adjusting the processes and modalities used to deliver programs and services to older adults through the aging social services network. The COVID-19 pandemic has highlighted the need for clinical and community-based organizations to unite and form inter-sectorial partnerships to maintain the provision of services and programs for engaging and supporting older adults during this difficult time of physical distancing and shelter-in-place and stay-at-home orders. The aging social services network provides a vital infrastructure for reaching older underserved and/or marginalized persons across the U.S. to reduce social isolation. Capitalizing on existing practices in the field, older adults can achieve distanced connectivity to mitigate social isolation risk while remaining at safe physical distances from others.